Low energy availability and cardiovascular disease risk in elite female rugby players: An observational study - Christensen, S.; Black, K.; Baker, D.; Sims, S.; Smith, B.; Kumar, J.; Groom, J. (Sport and Exercise Science New Zealand Conference, 2018, 2018)
Extensive research exists regarding LEA and both bone health and reproductive function; however, research is limited regarding the cardiovascular effects. Research to date, mostly in individual endurance sports, has investigated blood lipids, flow mediated dilation, and questionnaire data, which provide some evidence that LEA is associated with unfavourable lipid profiles and endothelial dysfunction. The aim of this study was to describe the lipid and arterial stiffness profiles of elite New Zealand female rugby players with and without LEA. Twenty-one elite female rugby Sevens players participated in the study. LEA status was assessed using the LEAF-Q questionnaire. Cardiovascular health was assessed through blood lipid profiles and pulse wave velocity to assess arterial stiffness. Results indicated trends towards lower HDL, -0.26 mmol/L (0.06, -0.57) and higher triglycerides, 0.22 mmol/L (0.48, -0.03) in those at risk for LEA compared to those not a risk. A trend towards higher pulse wave velocity was also seen in those at risk compared to those not a risk, 0.86 ms-1 (2.40, -0.68). These results suggest that elite female rugby Sevens athletes in New Zealand at risk for LEA show trends towards poorer cardiovascular health.